BENTUK NILAI MULTIKULTURAL DALAM KERJASAMA ANTAR PEMELUK AGAMA (Telaah Kritis Ayat-ayat dalam Perspektif Studi Qur’an Multikultural) - Aprilita Hajar (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
In this discussion, the researcher examines related forms or ways in living multicultural values, with cooperation between religious believers, because cooperation will foster tolerance, which is already supposed to be done by every human being, because humans are social creatures, which certainly need others, and here the researcher discusses using the perspective of multicultural Qur'an studies. In this discussion, the researcher uses qualitative research methods, which rely on literature review, with inductive research analysis. The source used by researchers is the Qur'an, which serves to explain, strengthen and prove that the form of multicultural values, in fact, is already contained in the Qur'an. The results of this study are, that in the life of mankind there are multicultural values, one of which is to revive the concept of tolerance and also a form of cooperation between religious believers, this is done to create a harmonious life among religious believers, and this has also been explained in the Qur'an, especially related to the attitude of tolerance between humans, or between religious believers. This form of cooperation between religious believers is actually allowed, but in order to still pay attention to the signs or restrictions that must be obeyed, especially about anything related to the rules of worship in each religion, or matters concerning principles in a religion and belief.